2018
DOI: 10.1093/ckj/sfy084
|View full text |Cite
|
Sign up to set email alerts
|

Comparing outcomes of biopsy-proven anti-neutrophil cytoplasmic autoantibody-associated glomerulonephritis patients treated with cyclophosphamide in the 20th and 21st centuries: a 23-year study

Abstract: BackgroundAnti-neutrophil cytoplasmic autoantibody (ANCA)-associated vasculitis (AAV) is a multisystem autoimmune disorder associated with significant morbidity and mortality. Approximately 80–90% of patients have circulating ANCAs. Long-term outcomes appear to be improving. This retrospective study analyses the incidence and patient outcomes over a period of 23 years at a single tertiary centre.MethodsOutcomes of patients diagnosed with AAV between 1 January 1988 and 31 December 2010 were collected retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…A recently published study on renal AAV showed better renal survival in a cohort of patients diagnosed in 2000-2010 compared to an older cohort diagnosed in 1988-1999 and significantly lower creatinine levels at diagnosis in the recent cohort, supporting this assumption [258]. Similar findings with improved renal survival paralleled by better renal function at diagnosis, indicating shorter diagnostic delay, have been reported also in other studies in ANCA-associated glomerulonephritis [183,259].…”
Section: Renal Survivalsupporting
confidence: 73%
“…A recently published study on renal AAV showed better renal survival in a cohort of patients diagnosed in 2000-2010 compared to an older cohort diagnosed in 1988-1999 and significantly lower creatinine levels at diagnosis in the recent cohort, supporting this assumption [258]. Similar findings with improved renal survival paralleled by better renal function at diagnosis, indicating shorter diagnostic delay, have been reported also in other studies in ANCA-associated glomerulonephritis [183,259].…”
Section: Renal Survivalsupporting
confidence: 73%
“…Overall, the proportion of renal involvement was similar to that reported in the literature [ 12 ]; however, in earlier reports, up to one-third of those with antineutrophil cytoplasmic antibody–associated vasculitis with renal involvement went on to develop end-stage renal disease [ 16 ] which was higher than what was found in this study (granulomatosis with polyangiitis: 73/457, 16.0%; microscopic polyangiitis: 18/135, 13.3%). This could be related to the improvement of renal outcomes in granulomatosis with polyangiitis and microscopic polyangiitis patients over time reflecting the changes in diagnosis and management [ 16 , 17 ]. This could also reflect the fact that there was a possible bias as a result of less morbidity in participants from the online portal.…”
Section: Discussionmentioning
confidence: 99%